STUDY OF PHYSICOCHEMICAL AND ORGANOLEPTIC PROPERTIES OF WET NOODLE WITH THE ADDITION OF KELAKAI LEAVES EXTRACT (Stenochlaena palustris) - Gustiani, Vanti; Putri, Rizky Febriyani; Yulinda, Ratna (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2022)
Kelakai (Stenochlaena palustris (Burm F) Bedd) is a fern plant found in swampy or wetlands. This study aims to determine the effect of adding kelakai extract to the production process of wet noodles on the physicochemical properties of elasticity, water absorption, and moisture content, as well as the organoleptic properties of aroma, color, and texture, in order to determine the optimal formula for kelakai extract in making wet noodles. This study was designed using a completely randomized design (CRD), which consisted of 4 treatments, namely F0 (0%), F1 (60%), F2 (80%), and F3 (100%). The data were analyzed using the Analysis of Variance (ANOVA) statistical test with a confidence level of α = 0,05. If there is a significant difference between the treatments, then continued with the Duncan Multiply Range Test (DMRT) to test the Physico-Chemical properties, and the Kruskal-Wallis statistical test with a confidence level of α = 0,05 for the organoleptic test. If there is a significant difference between the treatments, then proceed with the Mann-Whitney follow-up test using SPSS 25. The results showed that wet noodles with the addition of kelakai extract had a significant effect on elasticity and water absorption where the more extracts, the higher the elasticity and water absorption. Besides, it also having a significant effect on water content, where the more extracts, the lower the water content. The results of the research on the preference level test or organoleptic data showed no significant effect on the panelists' preference for color, aroma and texture. In general, the F2 treatment is the most ideal formulation.